1980
DOI: 10.21273/jashs.105.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light and Nitrogen and Potassium Levels on Growth and Light Compensation Point of Ficus benjamina L.1

Abstract: The effects of 2 light levels, (full sun and 47% shade) 3 nitrogen and 3 potassium levels (672, 2018, and 3362 kg/ha yr-1) on light compensation point, shoot and root growth, canopy distribution and leaf tissue nutrient content of Ficus benjamina were determined. The 47% shade treatment during 7 months of production significantly decreased light compensation point levels. N level slightly affected compensation point and K level had no effect. Higher N levels increased shoot growth, while K levels played a domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Weeping fig, widely grown as a foliage plant and extensively used for commercial interior plantscaping, often drops many leaves when moved from production to interior locations. The extreme reduction in light levels has been considered a major cause of subsequent leaf abscission and has led to studies regarding light acclimatization of Ficus (5,10,11).…”
mentioning
confidence: 99%
“…Weeping fig, widely grown as a foliage plant and extensively used for commercial interior plantscaping, often drops many leaves when moved from production to interior locations. The extreme reduction in light levels has been considered a major cause of subsequent leaf abscission and has led to studies regarding light acclimatization of Ficus (5,10,11).…”
mentioning
confidence: 99%
“…Low LCP and Rd rates for shade-grown weeping fig plants explain the observation (10) that shade-produced plants survive better in low-light interior environments than plants produced in full sun. Comparisons among the previous reports (7,15,17) on whole plant LCP of sun-and shade-grown weeping fig plants indicate considerable variation, but LCP cannot be compared directly due to differing units of measure. However, their results generally concur with those reported herein which indicate considerable potential for photosynthetic adaptation of weeping fig leaves to varying light environments.…”
Section: Pn (M8kc9 2 Dm 2 Tr (Gh2q Dm ~2 H R-1) Time Of Day ---------...mentioning
confidence: 78%
“…Collard et al (7) determined whole plant LCPs of weeping fig plants grown under 4 radiation levels and found that the LCP of 80% shade-grown plants was only 36% that of full-sun-grown plants. Other researchers (15,17) also reported lower whole plant LCPs for shade-grown weeping fig plants.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Collard et al (6) found that weeping fig plants grown under 80% shade had a LCP about one-third that of full-sun-grown plants. Johnson et al (17) and Joiner et al (18) reported that LCP of 47% shade-grown plants was less than that of full-sun-grown plants. Fonteno and McWilliams (13) reported that LCP and Rd of 4 sun-grown foliage species declined after transfer to a SIE for 4 to 15 weeks.…”
mentioning
confidence: 99%